Comparison of MAPIE versus MAP in patients with a poor response to preoperative chemotherapy for newly diagnosed high-grade osteosarcoma (EURAMOS-1): an open-label, international, randomised controlled trial. Issue 10 (October 2016) - Marina, Neyssa M; Smeland, Sigbjørn; Bielack, Stefan S; Bernstein, Mark; Jovic, Gordana; Krailo, Mark D; Hook, Jane M; Arndt, Carola; van den Berg, Henk; Brennan, Bernadette; Brichard, Bénédicte; Brown, Ken L B; et al.
Summary: Background: We designed the EURAMOS-1 trial to investigate whether intensified postoperative chemotherapy for patients whose tumour showed a poor response to preoperative chemotherapy (≥10% viable tumour) improved event-free survival in patients with high-grade osteosarcoma. Methods: EURAMOS-1 was an open-label, international, phase 3 randomised, controlled trial. Consenting patients with newly diagnosed, resectable, high-grade osteosarcoma aged 40 years or younger were eligible for randomisation. Patients were randomly assigned (1:1) to receive either postoperative cisplatin, doxorubicin, and methotrexate (MAP) or MAP plus ifosfamide and etoposide (MAPIE) using concealed permuted blocks with three stratification factors: trial group; location of tumour (proximal femur or proximal humerus vs other limb vs axial skeleton); and presence of metastases (no vs yes or possible). The MAP regimen consisted of cisplatin 120 mg/m 2, doxorubicin 37·5 mg/m 2 per day on days 1 and 2 (on weeks 1 and 6) followed 3 weeks later by high-dose methotrexate 12 g/m 2 over 4 h. The MAPIE regimen consisted of MAP as a base regimen, with the addition of high-dose ifosfamide (14 g/m 2 ) at 2·8 g/m 2 per day with equidose mesna uroprotection, followed by etoposide 100 mg/m 2 per day over 1 h on days 1–5. The primary outcome measure was event-free survival measured in the intention-to-treat population. This trial is registered withClinicalTrials.gov, numberNCT00134030 . Findings: Between April 14, 2005, and June 30, 2011, 2260 patients were registered from 325 sites in 17 countries. 618 patients with poor response were randomly assigned; 310 to receive MAP and 308 to receive MAPIE. Median follow-up was 62·1 months (IQR 46·6–76·6); 62·3 months (IQR 46·9–77·1) for the MAP group and 61·1 months (IQR 46·5–75·3) for the MAPIE group. 307 event-free survival events were reported (153 in the MAP group vs 154 in the MAPIE group). 193 deaths were reported (101 in the MAP group vs 92 in the MAPIE group). Event-free survival did not differ between treatment groups (hazard ratio [HR] 0·98 [95% CI 0·78–1·23]); hazards were non-proportional (p=0·0003). The most common grade 3–4 adverse events were neutropenia (268 [89%] patients in MAP vs 268 [90%] in MAPIE), thrombocytopenia (231 [78% in MAP vs 248 [83%] in MAPIE), and febrile neutropenia without documented infection (149 [50%] in MAP vs 217 [73%] in MAPIE). MAPIE was associated with more frequent grade 4 non-haematological toxicity than MAP (35 [12%] of 301 in the MAP group vs 71 [24%] of 298 in the MAPIE group). Two patients died during postoperative therapy, one from infection (although their absolute neutrophil count was normal), which was definitely related to their MAP treatment (specifically doxorubicin and cisplatin), and one from left ventricular systolic dysfunction, which was probably related to MAPIE treatment (specifically doxorubicin). One suspected unexpected serious adverse reaction was reported in the MAP group: bone marrow infarction due to methotrexate. Interpretation: EURAMOS-1 results do not support the addition of ifosfamide and etoposide to postoperative chemotherapy in patients with poorly responding osteosarcoma because its administration was associated with increased toxicity without improving event-free survival. The results define standard of care for this population. New strategies are required to improve outcomes in this setting. Funding: UK Medical Research Council, National Cancer Institute, European Science Foundation, St Anna Kinderkrebsforschung, Fonds National de la Recherche Scientifique, Fonds voor Wetenschappelijk Onderzoek-Vlaanderen, Parents Organization, Danish Medical Research Council, Academy of Finland, Deutsche Forschungsgemeinschaft, Deutsche Krebshilfe, Federal Ministry of Education and Research, Semmelweis Foundation, ZonMw (Council for Medical Research), Research Council of Norway, Scandinavian Sarcoma Group, Swiss Paediatric Oncology Group, Cancer Research UK, National Institute for Health Research, University College London Hospitals, and Biomedical Research Centre.